FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGUSAHAKAN PADI ORGANIK DI DESA KARANG SARI KECAMATAN BELITANG III KABUPATEN OKU TIMUR - Andriani, Ria; Sobri, Khaidir; Iswarini, Harniatun (Muhammadiyah University of Palembang, 2018)
ABSTRACTThis study aims to determine the factors that influence the decision of farmers in organic rice cultivation, and to find out how much income farmers cultivate paddy organic and non organic. This research was conducted in Karang Sari Village Belitang III District of East OKU District from July to August 2017. The research method used was survey, while the sampling method used was disproportionate stratified random sampling method with 44 respondents. Methods of data collection used observation and interview methods. The data obtained in the field first grouped then processed by tabulation. To answer the first problem is done mathematical model and described descriptively with logit model regression equation. Furthermore, to analyze and compare the income of organic rice farmers and non-organic rice used parametric analysis with t-test. Statistical test is done by using computer application program SPSS for windows 16,00. Result of research that simultaneously factor influencing decision of farmer age, land area, education, motivation have real effect to farmer decision. Partially age and motivation have a significant effect on the decision, while the area of land and education has no significant effect on the decision of farmers to cause organic rice. Revenue received by organic rice farmers is greater than that of non-organic paddy farmers extending cultivation or per hectare per planting season in accordance with the hypothesis